The Effect of GS‐548351 on the Pharmacokinetics of Midazolam Following Multiple Doses of ANS‐6637 in Healthy Adults. (23rd June 2020) - Bunn, Haden T.; Rosenthal, Elana; Mathur, Poonam; McLaughlin, Mary; Proschan, Michael; Vijan, Arjun; Aepfelbacher, Julia; Kottilil, Shyamasundaran; Masur, Henry; Kattakuzhy, Sarah; George, Jomy M.
Abstract: ANS‐6637, a pro‐drug of GS‐548351, is a selective, reversible inhibitor of aldehyde dehydrogenase isoform 2 under development as an anticraving agent for the treatment of substance use disorders. In vitro testing indicates that GS‐548351 is an inhibitor and inducer of cytochrome P450 family 3, subfamily A (CYP3A). In this phase 1 single‐center, open‐label, fixed‐sequence drug‐drug interaction study we assessed the impact of steady‐state GS‐548351 on single‐dose pharmacokinetics of midazolam, an index substrate for CYP3A. Twelve healthy volunteers received 600 mg of ANS‐6637 by mouth daily from study days 3 to 8 and a single 5‐mg oral dose of midazolam on days 1 and 8. Pharmacokinetic samples were collected over 24 hours on days 1 and 8, then analyzed using liquid chromatography‐tandem mass spectrometry. The prespecified no‐effect range for the 90% confidence interval (CI) of the geometric mean ratio (GMR) of midazolam coadministered with ANS‐6637 (day 8) compared with midazolam alone (day 1) was 0.7‐1.43. There was an increase in midazolam AUC0‐∞ (GMR [90%CI]) that was within the no‐effect range (1.26 [1.12‐1.425]) and an increase in midazolam Cmax that was outside the range (1.22 [1.03‐1.45]). The AUC0‐∞ (1.08 [0.91‐1.27]) and Cmax (0.95 [0.75‐1.2]) of 1‐hydroxymidazolam, the primary metabolite of midazolam, were also within the no‐effect range. A single grade 3 adverse event (alanine aminotransferase elevation) was identified and resolved following discontinuation of the study drug. Overall, multidose ANS‐6637 was well tolerated and did not alter the PK of midazolam beyond a small increase in AUC0‐∞ that is unlikely to be clinically significant.